Approval of non-tender work of dismantling of guide wall - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC Joint Venture for approval of non-tender work of dismantling of guide wall of Brac University new campus project.